Genetic diversity for drought and low-phosphorus tolerance in rice (Oryza sativa L.) varieties and donors adapted to rainfed drought-prone ecologies - Somnath Roy (Nature Portfolio, 2021)
Abstract Drought and phosphate availability are two major abiotic factors limiting productivity of rice in rainfed upland areas. There has been a constant need for new improved donor with tolerance to multiple abiotic stress conditions for rainfed rice breeding. In the present study, a set of 32 popular rice varieties and landraces were evaluated for drought and low-phosphorus (P) tolerance, and also characterized using grain yield under reproductive drought QTLs (DTY QTLs) and Pup1 linked/specific molecular markers. Twenty-seven genotypes were identified as tolerant to moderately tolerant to drought. The SSR markers linked to ten DTY QTLs classified the genotypes into two groups corresponding to aus and indica. The tolerant genotypes were distributed under both groups. Based on the core markers of Pup1 locus, complete tolerant haplotype was recorded in nine genotypes other than the tolerant check Dular. Nine more genotypes showed the incomplete tolerant haplotypes. The rice genotypes showed significantly high genetic variability for low-P tolerance in hydroponic study. A few genotypes revealed non-Pup1 type tolerance which needs further confirmation.